2017
DOI: 10.3892/or.2017.5362
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inhibition is associated with OPN/MMP-9 downregulation in cutaneous melanoma

Abstract: The development of cutaneous melanoma is influenced by genetic factors, including BRAF mutations and environmental factors, such as ultraviolet exposure. Its progression has been also associated with the involvement of several tumour microenvironmental molecules. Among these, nuclear factor-κB (NF-κB) has been indicated as a key player of osteopontin (OPN) and matrix metalloproteinase-9 (MMP-9) activation. However, whether NF-κB plays a role in the development and progression of melanoma in association with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 71 publications
0
65
0
Order By: Relevance
“…Cutaneous melanoma is one of the most aggressive forms of skin cancer and one of the leading causes of cancer-related mortality due its metastatic power. Several studies have demonstrated that melanoma spreading is the result of genetic mutations and tumor microenvironmental alterations, characterized by the overexpression of proteins able to favor tumor invasion and surrounding infiltration ( 39 44 ). In particular, a key role is played by the overexpression of matrix metalloproteinases (MMPs), particularly MMP-9 and MMP-2, that induces the degradation of the components of the extracellular matrix, thus favoring tumor cell infiltration and spreading through the bloodstream ( 40 42 ).…”
Section: Melanoma Biologymentioning
confidence: 99%
“…Cutaneous melanoma is one of the most aggressive forms of skin cancer and one of the leading causes of cancer-related mortality due its metastatic power. Several studies have demonstrated that melanoma spreading is the result of genetic mutations and tumor microenvironmental alterations, characterized by the overexpression of proteins able to favor tumor invasion and surrounding infiltration ( 39 44 ). In particular, a key role is played by the overexpression of matrix metalloproteinases (MMPs), particularly MMP-9 and MMP-2, that induces the degradation of the components of the extracellular matrix, thus favoring tumor cell infiltration and spreading through the bloodstream ( 40 42 ).…”
Section: Melanoma Biologymentioning
confidence: 99%
“…This process causes the production of inflammatory mediators that can cause or facilitate mutagenesis, uncontrolled cell proliferation, angiogenesis and cell degeneration responsible for neurodegenerative disorders and cancer (70)(71)(72). In addition, bacteria are able to modulate cell proliferation through activation of the nuclear factor κB (NF-κB) and the inhibition of cell apoptosis promoting or inhibiting the development of several cancer types (73)(74)(75).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%
“…MMPs are considered to be a crucial family of cell migration-associated proteins that degrade collagen and different components of the ecM, contributing to Kc migration and the eMT during wound healing (26,27). Previous studies have reported that the function of MMPs is regulated by numerous factors, including transcription factors, micrornas and methylation modifications (28)(29)(30). Furthermore, further studies have demonstrated that the transcription factor Foxo3a is associated with the negative regulation of the MMP-1 and MMP-9 genes (31,32).…”
Section: Discussionmentioning
confidence: 97%